(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Keratoconus (KC) is a degenerative noninflammatory disease of the cornea which is characterized be structural changes in the cornea which leads to progressive thinning and bulging in the central and/or peripheral part of the cornea and is accompanied by irregular astigmatism and significant vision impairment. Today, keratoconus treatment is focused on a stage of disease development. At progressive KC stages (II-III), corneal collagen cross-linking is performed. At the present, a latest-generation unit (UV-X™2000, Avedro) is used to perform accelerated cross-linking, which allows for a threefold decrease of the procedure duration (to 10 minutes) compared to the standard protocol Material and Methods. Corneal collagen cross-linking was performed in 71 patients (100 eyes). Results. Accelerated corneal collagen cross-linking for keratoconus stages II-III made it possible to stabilize the pathological process in 100% of cases, based on 12 month follow-up. Keratoconus stabilization was accompanied by: a decrease of astigmatism by 1.4 D and of the corneal refractive power by 3.2D; an increase of the corneal thickness by 8.8 nm; an increase of UCVA and BCVA in 96.5% and 89.6% of cases, respectively; and recovery of normal corneal architectonics according to confocal biomicroscopy data. Subjectively, 64 patients (90%) noted the improvement in the vision quality and better tolerance to spectacles correction.